Setting Properties of Calcium Phosphate Bone Cement. (2019) - Fathi, M.; Kholtei, A.; EL Youbi, S.; Chafik El Idrissi, B.
Abstract: Calcium phosphate cements (CPCs) are widely used in bone repair. CPCs show many advantages comparing to other calcium phosphate-based materials because of its chemical similarity to the mineral constituent of natural bone. This work describes a new apatitic calcium phosphate cement composition with a Ca/P ratio = 1.38, by mixing two components which were prepared by wet chemical synthesis methods. One component is chemically synthesized by mixing α-tricalcium phosphate (αTCP, Ca3 (PO4 )2 ) and HA (Ca10 (PO4 )6 OH)2 ), while the second component is again a chemically synthesized single phase DCPD (CaHPO4 .2H2 O) powder. The sitting solution used is 3 wt% Na2 HPO4 . 2H2 O dissolved in distilled water with a liquid to powder ratio L/P = 0.4. The cement was characterized in terms of setting time, compressive strength. XRD and SEM techniques were employed to evaluate the phase composition and surface morphology of the cement, the powder XRD data shows that the cement sample soaked in water has transformed into calcium deficient hydroxyapatite. The cement showed a fast setting time (14 min), this cement also showed a high compressive strength (35 MPa).